Model Pembelajaran Problem-Based Learning pada Materi Tumbuhan : Penelitian Tindakan Kelas di SMA Negeri 1 Nanusa - Angellia Manein; Meike Paat; Mercy Rampengan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to assess how well the Problem-Based Learning learning model improves the learning outcomes of Science High School Negeri 1 Nanusa grade XI students studying the Structure and Function of Plant Tissues. Learning biology frequently calls both a thorough conceptual grasp as well as an instructional strategy that may best engage pupils. The Classroom Action Research methodology is used in this study in two cycles, each with two meetings. Pre-tests, post-tests, observation of teacher and student activities, and documentation of the learning process were used to gather data. The study's findings demonstrated that using the Problem-Based Learning paradigm improved student learning outcomes' average score from 70 in the first cycle to 82 in the second. Additionally, the percentage of classical completeness rose dramatically from 40% to 90%. Furthermore, the second cycle appeared to have better results regarding students' active participation in group discussions, comprehension of the subject matter, and capacity to communicate group work outcomes. These results suggest that biology instruction at the secondary school level benefits greatly from using problem-based learning. This methodology promotes students' active participation, conceptual comprehension, and improved academic performance.